CONTRIBUTION OF RURAL WOMEN EDUCATION LEVELS TO FOOD SECURITY IN LIKUYANI SUB COUNTY, KAKAMEGA COUNTY, KENYA - Chebuche, Edwin; Wakhungu, Jacob (European Journal of Gender Studies, 2021)
Purpose: Rural women play an essential role in the four pillars related to food security: availability, accessibility, utilization and stability. However, there is a gender gap in access to resources such as: land, energy, technology, credit, pesticides and fertilizers. The overall objective of this study was to evaluate the contribution of rural women education levels to food security in Likuyani sub county, Kakamega County, Kenya. Methodology: This study was carried out in Kakamega County, Likuyani sub-county. This study used cross-cultural research design. The study population consisted of 30,685 respondents. The study sampled 395 using simple respondents using random sampling. Data was collected using structured questionnaires and focused group discussion guides. Content validity was tested by experts while reliability was tested at 0.7. Data was analysed using both descriptive and inferential statistics using SPSS version 24 and presented using APA tables. Findings: The research hypothesis posited H1: the level of education of rural women has no significant influence on food security in Likuyani sub-county was rejected using both r and R2. From the results, the level of education of rural women had significant positive effect on food security. Therefore, the hypothesis was rejected. In general, it was revealed that educational empowerment of rural women had largest unique significant contribution to the model. Recommendations: The researcher recommends that Government and other stakeholders should endeavor to put in place deliberate measures to empower women and girls especially on agriculture as a livelihood to foster food security through Women empowerment projects like women fund. Health organizations should sensitize women on the importance of family planning since larger families put a strain on the available resources. Women should be empowered to have access and control and even ownership of factors of production in partnership with men to enhance their efforts towards household food production and security.